2003
DOI: 10.1210/en.2002-221039
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Signal-Regulated Kinase 1/2 Activation by Myometrial Oxytocin Receptor Involves GαqGβγ and Epidermal Growth Factor Receptor Tyrosine Kinase Activation

Abstract: The mechanisms by which oxytocin (OT) stimulates extracellular signal-regulated kinase 1/2 (ERK1/2) are only partially understood. OT receptor (OTR) signals predominantly through Galpha(q), but ERK1/2 phosphorylation (ERK1/2-P) in PHM1 myometrial cells was not eliminated by inhibition of downstream effectors such as phospholipase C or protein kinase C. Inconsistent with a Galpha(i)-coupled response, pertussis toxin inhibition of OT-induced ERK1/2-P was reversed by the protein kinase A inhibitors Rp-cAMPS and K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
55
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(62 citation statements)
references
References 49 publications
(61 reference statements)
7
55
0
Order By: Relevance
“…This study provides, to our knowledge, the first evidence for the transactivation of EGFR by OXTR in brain. This regulation has been demonstrated in myometrial and epithelial cells (Zhong et al, 2003;Krishnaswamy et al, 2010), where the EGFR tyrosine kinase may serve as an important effector in a signaling pathway connecting OXTR to PI3K and ERK1/2 to regulate gene expression. Interestingly, it was noted that the inhibition of PLC with U73122 completely prevented OXT-induced increases in PI3K and ERK1/2 activation, suggesting that OXTinduced PLC activation mediates the transactivation of EGFR and its downstream PI3K and ERK1/2 signaling.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…This study provides, to our knowledge, the first evidence for the transactivation of EGFR by OXTR in brain. This regulation has been demonstrated in myometrial and epithelial cells (Zhong et al, 2003;Krishnaswamy et al, 2010), where the EGFR tyrosine kinase may serve as an important effector in a signaling pathway connecting OXTR to PI3K and ERK1/2 to regulate gene expression. Interestingly, it was noted that the inhibition of PLC with U73122 completely prevented OXT-induced increases in PI3K and ERK1/2 activation, suggesting that OXTinduced PLC activation mediates the transactivation of EGFR and its downstream PI3K and ERK1/2 signaling.…”
Section: Discussionmentioning
confidence: 89%
“…Because OXT has been shown to transactivate EGFR tyrosine kinase in both PHM1 immortalized human myometrial cells (Zhong et al, 2003) and bovine endometrial epithelial cells (Krishnaswamy et al, 2010), we therefore examined whether activation of OXTR could transactivate EGFR and subsequently stimulate PKM protein synthesis. As expected, we found that pretreatment of the synaptoneurosomes with a tyrophostin AG1478 (1 M), a selective inhibitor of EGFR (Levitzki and Gazit, 1995), completely blocked OXT (1 M)-induced increases in PKM protein synthesis (Fig.…”
Section: Transactivation Of Egfr Is Required For Oxt-induced Enhancemmentioning
confidence: 99%
“…This may explain the spontaneous bursts at early stages of actindisrupting agent application and how OT could quickly increase the paranuclear cytosolic F-actin, but not membrane subcortical F-actin, in OT neurons in the presence of cytochalasin B. (Zhong et al, 2003;Wang and Hatton, 2007) and ERK kinase, MEK. pERK1/2 can facilitate F-actin formation through at least two pathways: by increasing production of prostaglandins (PGs) (Wang and Hatton, 2006) and by phosphorylating cofilin (P-cofilin) (phosphorylation of cofilin inhibits its ability to depolymerize F-actin) (Nebl et al, 2004;Pritchard et al, 2004).…”
Section: Actin Reorganization and Ot-evoked Burstsmentioning
confidence: 97%
“…In the signaling pathway for OT actions, pERK1/2 has been identified (Hoare et al, 1999;Zlatnik et al, 2000;Burns et al, 2001). OTR-associated G-protein ␤␥ subunits, a dominant signal in OT-evoked bursts (Wang and Hatton, 2007), can activate ERK1/2 by phosphorylation to form pERK1/2 (Zhong et al, 2003). Another major target of OT actions is actin.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation